Descriptive Cross-sectional Study on Mothers’ Knowledge Regarding Prevention of Neonatal Hypothermia - Shah, Indu; Paudyal, Laxmi; Soti, Harikala; Gautam, Nitu S (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION In today’s era neonatal hypothermia is ranked as high risk factor for newborn survival. Practicing kangaroo mother, mummifying newborn, delaying first bath etc are useful practices for maintaining warm chain and thermo-protection of newborns. MATERIAL AND METHODS A cross-sectional descriptive study was used for the study. Setting of the study was post natal ward of Gandaki Medical College Teaching Hospital and Research Center with total sample of 70. Probability convenient sampling technique was used for the study. Data analysis was done through descriptive and inferential statistics. RESULTS Among the respondents 41.4% mothers were of age between 26-30yrs, majority 75.7% were Hindu, 42.9% had completed secondary level education, more than half 51.4% were residing in nuclear family, 45.7% were housewife, more than half 52.9% had income/month as 15001-20000, more than half 61.4% had normal delivery, and more than half 51.4% had two children. Almost half of the mothers 45.7% of mothers had inadequate level of knowledge, 32.9% had moderate knowledge and 21.4% had adequate knowledge, also there showed significant association between mothers level of knowledge on neonatal hypothermia with educational status, type of family and type of delivery at 5% level (ie., p<0.05). CONCLUSION Based on the findings it is concluded that almost half of the mothers have inadequate knowledge regarding neonatal hypothermia. Mothers knowledge might be helpful to prevent newborn from neonatal hypothermia, so training should be provided to mothers and family members during their antenatal period regarding thermal protection of the newborn.